Phase II is Boss - Pires, BC (Daily Express)
BC Pires relates his night in the Phase II Pan Groove Panyard when Richard Bailey, the Whiz Kid, Ace drummer from Trinidad, via London, arrived for Carnival.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Popular music -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago